(untitled) (Journal of the Medical College for Women & Hospital, 2026)
Hailey- Hailey Disease (HHD), a rare genetic skin disorder, is inherited as autosomal dominant pattern. Abnormal epithelial cell adhesion due to altered calcium metabolism is the main pathology of the disease. Persistently recurrent, pruritic, painful, flaccid vesicles, bulla, pustules with crusted and erosive plaques along with maceration and fissuring are the clinically characteristic features of the disease which involve the neck, axilla, flexures and groins. the onset of the disease is common in late tensor early twenties. Characteristic clinical presentation and histopathological findings of “dilapidated brick wall” – are the aids to establish the diagnosis. Here we report a case of a 59-year-old woman with recurrent attack with the features consistent with HHD with positive family history and specific histopathological findings helped us to reach the final diagnosis. J Med Coll Women Hosp.2026; 22(1): 172-177